Medial temporal lobe damage impairs representation of simple stimuli - Warren, David E.; Duff, Melissa C.; Tranel, Daniel; Cohen, Neal J. (Frontiers in Human Neuroscience, 2010)
Medial temporal lobe damage in humans is typically thought to produce a circumscribed impairment in the acquisition of new enduring memories, but recent reports have documented deficits even in short-term maintenance. We examined possible maintenance deficits in a population of medial temporal lobe amnesics, with the goal of characterizing their impairments as either representational drift or outright loss of representation over time. Patients and healthy comparisons performed a visual search task in which the similarity of various lures to a target was varied parametrically. Stimuli were simple shapes varying along one of several visual dimensions. The task was performed in two conditions, one presenting a sample target simultaneously with the search array and the other imposing a delay between sample and array. Eye-movement data collected during search revealed that the duration of fixations to items varied with lure-target similarity for all participants, i.e., fixations were longer for items more similar to the target. In the simultaneous condition, patients and comparisons exhibited an equivalent effect of similarity on fixation durations. However, imposing a delay modulated the effect differently for the two groups: in comparisons, fixation duration to similar items was exaggerated; in patients, the original effect was diminished. These findings indicate that medial temporal lobe lesions subtly impair short-term maintenance of even simple stimuli, with performance reflecting not the complete loss of the maintained representation but rather a degradation or progressive drift of the representation over time.